Identification of AD‐18, 5F‐MDA‐19, and pentyl MDA‐19 in seized materials after the class‐wide ban of synthetic cannabinoids in China. Issue 2 (5th December 2021) - Liu, Cui‐Mei; Hua, Zhen‐Dong; Jia, Wei; Li, Tao
Abstract: To curb the manufacturing, trafficking, and abuse of synthetic cannabinoids, China implemented a class‐wide regulation on synthetic cannabinoids in July 2021. Recently, three different types of synthetic cannabinoid analogs that were not covered by the generic definitions were detected in seized powdered and e‐liquid materials. These derivatives included 2‐(2‐(1‐(4‐fluorobenzyl)‐1 H ‐indol‐3‐yl)acetamido)‐3, 3‐dimethylbutanamide (AD‐18), N ′‐(1‐(5‐fluoropentyl)‐2‐oxoindolin‐3‐ylidene)benzohydrazide (5F‐MDA‐19), and N ′‐(2‐oxo‐1‐pentylindolin‐3‐ylidene)benzohydrazide (pentyl MDA‐19). Identification was based on ultra‐high‐performance liquid chromatography–quadrupole time‐of‐flight–mass spectrometry (UHPLC–QTOF–MS), gas chromatography–mass spectrometry (GC–MS), nuclear magnetic resonance spectroscopy (NMR), and Fourier transform infrared spectroscopy (FT‐IR). AD‐18 is a methylene analog of ADB‐FUBICA. No chemical or pharmacological data about AD‐18 and 5F‐MDA‐19 have appeared until now, making this the first report on these two compounds. Pentyl MDA‐19 has previously been reported to have high affinity for cannabinoid CB1 and CB2 receptors, but this is the first report of its presence in the recreational drug market. Moreover, the collision‐induced dissociation (CID) and electron ionization (EI) characteristic fragmentation routes of AD‐18 and the other two MDA‐19 derivatives were also discussed to facilitate forensic laboratories in their identification of other substances with a similar structure in their case work. Abstract : Three synthetic cannabinoids AD‐18, 5F‐MDA‐19, and pentyl MDA‐19 were identified by UHPLC–QTOF–MS, GC–MS, NMR, and FT‐IR.